Two new species of the planthopper genus Eponisiella Emeljanov from China (Hemiptera, Fulgoromorpha, Meenoplidae) - Lv, Sha-sha; Yang, Lin; Chen, Xiang-Sheng (European Journal of Taxonomy, 2021)
Two new species of the genus Eponisiella Emeljanov, 1984 are described and illustrated from China (Guizhou and Shandong Provinces). These are E. dafangensis sp. nov. and E. shandongensis sp. nov., giving the genus eight species in total. A key to the species of Eponisiella is provided as well as a map of their geographic distribution, which is briefly discussed.